The effect of blended microlearning soil analysis practicum on students' learning outcomes in Geography - Yurotul Aidah; Ferryati Masitoh (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas PGRI Mahadewa Indonesia, 2026)
High schools with limited instructional resources require learning approaches that are both effective and practical. This study investigated the effectiveness of a blended microlearning model in improving students' learning outcomes during a soil analysis practicum in Geography. A quasi-experimental posttest-only control-group design was used with 59 Grade XI Social Science students at SMA Diponegoro Tumpang. Two classes were selected through purposive sampling: an experimental group (n = 30) that received blended microlearning instruction and a control group (n = 29) that followed conventional practicum-based learning. Data were collected using a cognitive achievement test, a psychomotor performance rubric, and a learning motivation questionnaire. The results show that students in the experimental group achieved a higher mean score (M = 87.3) than those in the control group (M = 79.3). Analysis using the Mann-Whitney U test indicated a statistically significant difference between the two groups (p = .019). These findings demonstrate that blended microlearning effectively enhances students' cognitive understanding, practical skills, and learning motivation in geography practicums. Therefore, this study recommends adopting microlearning-based blended strategies as a low-cost, feasible instructional alternative for schools with limited educational resources.